ANALISA PESTEL TERHADAP PENETRASI GOJEK DI INDONESIA - Paramadita, Siti; Umar, Abdullah; Kurniawan, Yohanes Jhony (Jurnal Pengabdian dan Kewirausahaan, 2020)
With the rapid development of the digital world today, of course, it will affect people's lives, like what used to be offline is now online. One of them that experienced a change from offline to online is the land transportation business. This is evidenced by changes in the base motorcycle taxi, with the digitization of the emerging online motorcycle taxis, such as GOJEK and GRAB. Where is this online motorcycle taxi using mobile applications to make transactions? These changes, of course, will have a significant impact on people's lives, whether it be on political, economic, social, technological, legal or environmental factors or commonly referred to as PESTEL. Therefore the purpose of this study is to analyze the extent to which the factors that influence the presence of GOJEK in Indonesia, especially those related to PESTEL. Where GOJEK is one of the start-up companies that have developed quite rapidly in the last 9 years. Starting from a motorcycle taxi call center service in 2010, until now, GOJEK has expanded its business to neighboring countries such as Singapore, Thailand, Malaysia, and Vietnam. Where research methods are carried out using a qualitative approach, which includes interviews, literature review and observation. Of course, with the very rapid development of GOJEK. Many impacts are caused by GOJEK. One of them is the economic impact, which with the existence of GOJEK, helps the development of SMEs. Where the support of GOJEK is to facilitate the delivery of goods produced by SMEs to buyers and the delivery process is faster. Keywords: Startup, PESTLE Analysis, Online Transportation, Mobile Application